Retrospective exploration of risk factors for L5 radiculopathy following lumbar floating fusion surgery. Issue 1 (December 2015) - Orita, Sumihisa; Yamagata, Masatsune; Ikeda, Yoshikazu; Nakajima, Fumitake; Aoki, Yasuchika; Nakamura, Junichi; Takahashi, Kazuhisa; Suzuki, Takane; Ohtori, Seiji
Abstract Background Lumbar floating fusion occasionally causes postoperative adjacent segment disorder (ASD) at lumbosacral level, causing L5 spinal nerve disorder by L5-S1 foraminal stenosis. The disorder is considered to be one of the major outcomes of L5-S1 ASD, which has not been evaluated yet. The present study aimed to evaluate the incidence and risk factors of postoperative L5 spinal nerve disorder after lumbar interbody fusion extending to the L5 vertebra. Methods We evaluated 125 patients with a diagnosis of spondylolisthesis who underwent floating fusion surgery with transforaminal lumbar interbody fusion with average postoperative period of 25.2 months. The patients were regarded as symptomatic with postoperative L5 spinal nerve disorder such as radicular pain/numbness in the lower limbs and/or motor dysfunction. We estimated and compared the wedging angle (frontal view) and height (lateral view) of the lumbosacral junction in pre- and postoperative plain X-ray images and the foraminal ratio (ratio of the narrower foraminal diameter to the wider diameter in the craniocaudal direction) in the preoperative magnetic resonance image. Risk factors for the incidence of L5 spinal nerve disorder were explored using multivariate logistic regression. Results Eight of the 125 patients (6.4 %) were categorized as symptomatic, an average of 13.3 months after surgery. The wedging angle was significantly higher, and the foraminal ratio was significantly decreased in the symptomatic group (bothP < 0.05) compared to the asymptomatic group. Multivariate logistic regression analysis of possible risk factors revealed that the wedging angle, foraminal ratio, and multileveled fusion were statistically significant. Conclusions Higher wedging angle and lower foraminal ratio in the lumbosacral junction were significantly predictive for the incidence of L5 nerve root disorder as well as multiple-leveled fusion. These findings indicate that lumbosacral fixation should be considered for patients with these risk factors even if they have few symptoms from the L5-S1 junction.